PERANCANGAN SISTEM STERILISASI ALAT KEDOKTERAN GIGI DENGAN METODE IONISASI - Linoval , M. Dilan; Maulana, Eka; Djuriatno, Waru (Jurnal Mahasiswa TEUB, 2024)
Health problems in Indonesia are still a concern due to the large number of deaths due to cross-infection diseases. In dentistry, the risk of cross infection often occurs because the use of dental instruments that are exposed to saliva is less than optimal in the sterilization process. Currently, the most frequently used sterilization tool in dentistry is the autoclave. Routine autoclave sterilization is usually operated at a steam pressure of 15 lb/in2. At this pressure, the temperature becomes 121oC. the time required at this temperature is 15-20 minutes (Volk and Wheeler, 1993). However, autoclaves are considered less effective because they have several disadvantages, such as being expensive, using high power, and requiring a lot of time to use. Therefore, it is necessary to have a solution to overcome the above problems. A research was carried out on designing a sterilization system for dental instruments using the ionizer method in order to determine the level of efficiency of this method in the process of sterilizing dental instruments. This sterilizer utilizes high voltage in the ion generator circuit to produce ions. This research was carried out by testing the working components and using an oscilloscope to determine the working parameters produced in the ionization circuit as well as testing in the microbiology laboratory to determine the effectiveness of the system in decontaminating bacteria. The results of this research are that the DHT22 sensor has an accuracy of 99.71% in detecting the temperature of the sterilization room and it was found that within an ion irradiation time of 300 seconds the number of bacteria was reduced by 97.32%. Keywords: ionization, dental tools, Sterilization